PENGARUH KOMPETENSI PROFESIONAL DAN EFIKASI GURU TERHADAP KOMITMEN PROFESIONAL DIMODERASI BUDAYA ORGANISASI SEKOLAH (Studi pada SMA Islam Sultan Agung Semarang) - T a r n o, T a r n o; Fauzan, Mohammad (Jurnal Ilmiah Telaah Manajemen, 2018)
The purpose of this study is to examine and analyze the influence of professional competence and teacher efficacy on professional commitment moderated school organizational culture on teachers of Sultan Agung 1, 2 and 3 Islamic High Schools Semarang. The population in this study are teachers of Sultan Agung 1, 2 dan 3 Islamic Senior High School totaling 136 people. Research data is primary data obtained directly from respondents with a questionnaire. Data analysis method uses Moderation Regression Analisys (MRA) absolute difference model. The results show that professional competence does not have a positive effect on professional commitment. The efficacy of teachers has a positive effect on professional commitment. School organizational culture has a positive effect on professional commitment. School organizational culture does not moderate the influence of professional competence on professional commitment. School organizational culture does not moderate the effect of teacher efficacy on professional commitment. Keywords: professional competence, teacher efficacy, school organizational culture and professional commitment.